1978
DOI: 10.1148/129.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Transhepatic Dilatation of Choledochoenterostomy Strictures

Abstract: During the last seven years percutaneous transhepatic biliary drainage (THD) was used in 13 patients to relieve obstructive jaundice caused by postsurgical stricture. Nine patients had internal drainage with dilatation, and external drainage alone was feasible or available in 4 patients. Of these 4, 2 had further reconstructive surgery without lasting results, jaundice was not completely relieved in 1 because of biliary cirrhosis, and 1 died in hepatic coma from sclerosing cholangitis. Eight patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 0 publications
2
18
1
1
Order By: Relevance
“…1). Balloon dilatation of postoperative biliary strictures in nontransplant patients is safe, with reported success rates of 85-89% [21,22]. Similarily, we have found the procedure to be safe and effective in transplants.…”
Section: Discussionsupporting
confidence: 73%
“…1). Balloon dilatation of postoperative biliary strictures in nontransplant patients is safe, with reported success rates of 85-89% [21,22]. Similarily, we have found the procedure to be safe and effective in transplants.…”
Section: Discussionsupporting
confidence: 73%
“…In adults, Gruntzig angioplasty balloon catheters have been used in the dilatation of narrowed blood vessels [1], bile ducts [2,3], ampulla of vater [4], biliary-enteric anastomoses [5,6], and esophageal strictures [7]. In children, there have been fewer reports of the use of Gruntzig balloons but they have been used successfully to dilate bilial3r [8] and esophageal strictures [9].…”
mentioning
confidence: 99%
“…Molnar and Stockum [3], in 1978, first reported balloon dilatation of choledochoenterostomy strictures in 9 patients using a Teflon caged balloon catheter. More recently, Martin et al [4] reported 2 cases successfully treated using the Grfintzig balloon catheter.…”
Section: Discussionmentioning
confidence: 99%